A defesa no processo penal militar - Silva, Edson Nalon (2010)
After almost twenty years of active service in the Military Police of São Paulo before a shortage of doctrine of Military Criminal Procedure, we believe it is necessary to deal with some aspects of the Military Law, as the history of Military Justice in Brazil and São Paulo, the Constitutional Principles guiding the Criminal Procedure and the Military Penal Procedure, the composition of the State Military Justice, the jurisdiction of the Military Judicial Police, but, above all and mainly, discuss the legal and military criminal defense in the Military Penal Procedure, highlighting themes rarely visited by academic researchers, such as types of defense, rights of the accused, bail and parole, kinds of resources, defense in Military Administrative Law, crime of desertion and defense of the deserter, knowing some types of prisons under military criminal law and the issue of defense in the Military Police Inquiry